Managing Fairness Concerns in Resource Allocation Decisions: The Case for Transparency - Jared NAI (Institutional Knowledge at Singapore Management University, 2015)
Organizations keep allocation to peers secret to manage fairness concerns. We propose that secrecy can be self-defeating because people inflate expectations in the mere presence of a peer despite ignorance of allocation to peers.